Implementation Of New Service Development In The Electronic-Based Government System (Spbe) In Sumedang Regency - Engkus; Adit Aditiya Azhar Pratama; Citra Dwi Lestari; Eka Fikry Alhuda (Jurnal Dialektika: Jurnal Ilmu Sosial, 2023)
Abstract In this modern digital age, information technology has brought about significant changes in various government functions. One of the notable transformations is seen in the public service system, where the introduction of New Service Development products has led to the implementation of the Electronic Based Government System (SPBE) in Indonesia. This development is closely tied to the regulations outlined in PERPRES NO.95 of the Year 2018, which pertains to Electronic-Based Government Systems (SPBE). The primary objective of this research is to assess the extent to which the New Service Development, represented by SPBE, has been adopted in the Sumedang Regency. The evaluation aims to determine whether the implementation aligns with appropriateness and whether SPBE has been executed effectively, efficiently, and accountability. The research methodology employed is qualitative in nature, focusing on detailed and in-depth descriptions and explanations of the subject under study. Data for this research was gathered through a review of relevant literature and direct observation techniques, including interviews. Based on the data, observations, and field assessments, it is evident that the Sumedang Regency Government has made significant strides in the successful implementation of the Electronic Based Government System (SPBE). This success is attributed to the incorporation of solution features and innovations such as service integration through WA Kepo and the Command Center. These initiatives have enabled the Sumedang Regency Government to achieve the top position in SPBE at the national level in 2022. However, it is important to note that there is room for improvement, as there are areas that still require enhancement to further optimize services provided by the Sumedang Regency Government. Keywords: Electronic Based Government System, New Service Development, Technology